2003
DOI: 10.1007/s00705-002-0932-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fusion activity of influenza A haemagglutinin mediated by HA2-specific monoclonal antibodies

Abstract: The effect of seven monoclonal antibodies (MAbs) specific to the light chain (HA2) of influenza A haemagglutinin (HA) on its fusion activity was investigated. These MAbs, which are non-virus neutralizing, defined four distinct antigenic sites on HA2 glycopolypeptide and the corresponding epitopes were attributed to the sequence stretches on HA2. The accessibility of all seven HA2 epitopes significantly increased after trypsin cleavage and pH 5 treatment of the HA (X-31). The influence of anti-HA2 MAbs on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 22 publications
0
50
0
1
Order By: Relevance
“…Type I fusion proteins contain a hydrophobic sequence, known as the fusion peptide (FP), at or near the new amino-terminal region created by the cleavage event (57,62,76), and their final (postfusion) state contains a characteristic ␣-helical coiled-coil core structure corresponding to a heptad repeat motif (12,57). In recent years, these structures have been targets for the development of new antiviral drugs, including fusion-inhibiting peptides and antibodies (20,50,82), suggesting that fusion proteins might be important candidates both for vaccination and as therapeutic targets.…”
Section: Infectious Salmon Anemia Virus (Isav) Is An Enveloped Virusmentioning
confidence: 99%
“…Type I fusion proteins contain a hydrophobic sequence, known as the fusion peptide (FP), at or near the new amino-terminal region created by the cleavage event (57,62,76), and their final (postfusion) state contains a characteristic ␣-helical coiled-coil core structure corresponding to a heptad repeat motif (12,57). In recent years, these structures have been targets for the development of new antiviral drugs, including fusion-inhibiting peptides and antibodies (20,50,82), suggesting that fusion proteins might be important candidates both for vaccination and as therapeutic targets.…”
Section: Infectious Salmon Anemia Virus (Isav) Is An Enveloped Virusmentioning
confidence: 99%
“…An immune response can also be directed against the stalk of the influenza virus HA, but antibodies of this type are typically less abundant and less potent than are antibodies specific for the globular head. Nonetheless, antistalk antibodies can provide protection through passive transfer in animal models (7)(8)(9)(10)(11)(12)(13)(14). Whereas globular head antibodies can neutralize virus by preventing binding to the host cell, antistalk antibodies have been shown to act by preventing the fusion step of virus entry (13)(14)(15).…”
mentioning
confidence: 99%
“…Moreover, there are some regions of hA2 gp, which are conserved also among various subtypes (varečková et al, 2002, 2008). As we have shown previously, hA2 gp is immunogenic and able to induce a protective antibody response in mice (varečková et al, 2003a;Gocník et al, 2008). The most conserved part of hA2 gp is its n-terminus, FP.…”
Section: Introductionmentioning
confidence: 55%
“…In our previous studies we have shown that MAbs specific to hA2 gp, which are cross-reactive with different virus subtypes, inhibit the fusion activity of hA and reduce virus replication in vitro (varečková et al, 2002, 2003aStropkovská et al, 2009). these MAbs, when passively applied, protected mice against lethal infection with IAvs of homologous or heterologous hA subtype (Gocník et al, 2007;Janulíková, unpublished data).…”
Section: Discussionmentioning
confidence: 90%